(untitled) (KULT_online, 2010)
In his PhD study, historian Markus Roth presents research on the career paths and ruling practices of leading figures in country and district government in occupied Poland during the Second World War. Roth’s collective-biographical study is a new and interesting aspect of the mass of literature about German occupation politics in 1939-1945. The work of detailed research shows the men behind the institution of civil government in Poland and the development of their careers before and after the Nazi Regime.